PERMA NOMOR 4 TAHUN 2014 SEBAGAI TEROBOSAN DALAM PENGATURAN DIVERSI DI SISTEM PERADILAN PIDANA ANAK - Jihan Nabilah Wahid, (2022)
Children who commit criminal acts when put in prison sometimes do not deter the child, but make the child a more professional criminal. In addition, children have the right to continue to live, grow, and develop optimally. So cases of children dealing with the law must be resolved with a restorative justice approach. Restorative justice in the juvenile criminal justice system in the diversion model. Diversion is the settlement of children's cases from the judicial process to outside the criminal justice process. Hopefully an agreement can be reached between the two parties and a restoration of the situation as before. Implementation of diversion in Law Number11 of 2012 concerning the Juvenile Criminal Justice System is limited by the provisions in Article 7 paragraph 2 which states that diversion can only be carried out if the threat of imprisonment is charged to children under 7 (seven) years and not recidivist. Therefore, the Supreme Court of the Republic of Indonesia issued PERMA Number 4 of 2014 concerning Guidelines for Implementing Diversion in the Juvenile Criminal Justice System as an opportunity for children to be able to do diversion. This study uses a normative juridical research method. The results of this study indicate that the philosophical, juridical and sociological foundations in PERMA Number 4/2014. The Supreme Court anticipates that if a child actually commits a crime, diversion can be attempted and provide justice for the child. In addition, looking at Article 79 of the Law on the Supreme Court, it states that the Supreme Court can further regulate things that need to be done to start the administration of justice if there are things that have not been regulated in the law and the most important thing is to pay attention to what is best for the child.